Climate Smart Governance Dashboard: technical guide - Alahacoon, Niranga; Amarnath, Giriraj (International Water Management Institute, 2023)
The Climate-Smart Governance (CSG) Dashboard stands as an innovative platform, providing data on climate-related hazards, vulnerability, climate scenarios, and sector-specific information. Developed as part of the CGIAR initiative on Climate Resilience (ClimBeR), the CSG Dashboard plays a crucial role in supporting nations undertaking the UNFCCC National Adaptation Plan (NAP) process. Aligned with the iterative nature of the NAP process, the CSG Dashboard enhances adaptive capacity and resilience, minimizing vulnerability to climate change impacts. The training manual aims to guide users through the platform, ensuring ease of use and a clear understanding of its functionalities. The homepage offers an overview of the project, collaborative partners, and statistical data. Users register to access country-specific information. The landing page includes sections such as About Us, Our Team, Resources, Language, and Login. The platform comprises eight main subpages, including Country Overview, Climate Outlook, Project Tracker, Geo Intelligence Tools, Monitoring and Evaluation, Development Indicators, Adaption Catalog, and Investment Portfolio Planning. Users can navigate through these modules for detailed information, facilitated by the "View More" option. This module provides a comprehensive snapshot of a country, including water resources, agriculture, ecosystems, health, and climate hazards. It incorporates vital indicators like Human Development Index, electricity access, internet usage, and adaptive capacity. Historical and future climate data offer insights into the environmental and socio-economic landscape. Utilizing UNFCCC Shared Socioeconomic Pathways, this module projects a nation's risk under different climate policies and regions. Sub-modules include Climate Risk Profile, Future Climate Risk, Climate Risk Visualizer, and Climate Sectoral Impacts, allowing users to explore forecast predictions for climate variables. A powerful visualization tool, the Project Tracker aids in systematically monitoring adaptation, mitigation, and cross-cutting initiatives. Users can assess projects, identify successful strategies, and explore project details by category. The module also allows searching and viewing projects on a map. This component serves as a dynamic hub for overseeing climate change projects, enabling input, organization, and visualization of project data. Users can add, modify, delete projects, and view progress and reports associated with outcomes. This page offers detailed country-level information on geospatial data. Users can visualize, analyze, and interpret data, tailoring exploration with filters and comparing hazard and risk indicators. Administrative boundaries, project distribution, hydrology, infrastructure, hazard, and risk indicators are available. Users can explore individual Sustainable Development Goals (SDGs) in detail, assessing a country's progress towards meeting UN SDGs. The module guides monitoring, and evaluation teams and allows users to select specific SDGs for trend analysis. Showcasing global climate adaptation projects, this module encourages users to contribute project information. Users can visualize project distribution on a map, filter projects, and view individual project details. This module evaluates a country's economy and climate-related risks, focusing on GDP impacts across different climate scenarios. Policymakers can analyze potential financial implications and attract donor investment. The CSG Dashboard, developed under the CGIAR initiative, serves as a comprehensive solution, addressing challenges in climate-related initiatives. By consolidating data, providing planning tools, and adopting collaboration, it plays a critical role in enhancing adaptive capacity, resilience, and informed governance. The interconnected modules create a responsive and user-friendly platform, empowering stakeholders to make informed decisions and contribute to climate resilience globally.